Deer remains from the Middle Pleistocene site of Gruta da Aroeira (Portugal): Iberian faunal endemism and implications for hominin paleobiogeography - Croitor, Roman (2019)
The article presents a description of cervid remains from the Middle Pleistocene Acheulean site of Gruta da Aroeira (= Galerias Pesadas) in central Portugal. The assemblage comprises the remains of four deer species: Cervus elaphus, Praedama cf. savini, Haploidoceros mediterraneus, and Dama cf. vallonnetensis, making Gruta da Aroeira the first site in the Iberian Peninsula at which the genus Haploidoceros has been documented in the Middle Pleistocene. Virtually all the cervids documented at the site demonstrate a degree of endemism, including evolutionary modifications of skull, antlers and dentition or a reduction in body size. The unusual richness of the cervid community at Gruta da Aroeira may be related to the specific biogeographic conditions of the Middle Pleistocene in Iberia. Thus, while the Iberian Peninsula’s geographical link with the temperate west Eurasian zone facilitated the dispersal of cervids of palearctic origin into Iberia, it impeded the dispersal of ruminants from warmer, more arid areas. The endemic character of the Middle Pleistocene cervids and the biodiversity of the Iberian Peninsula should shed some light on the paleobiogeography of Iberian hominins and their role in hominin hunting or their economic strategies.